Generation Z Satisfaction with the Government's First 100 Days: The Mediating Role of Perceptions of Public Opinion on Social Media - Dian Amalia Putri; Putriaji Hendikawati (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2026)
The first 100 days of the Kabinet Merah Putih administration represent the initial phase of implementing the Asta Cita national development agenda. This period provides an important opportunity to evaluate public responses, particularly among Generation Z, a digitally active demographic that plays a strategic role in contemporary democracy. This study examines the influence of perceived government policies implemented during the first 100 days on Generation Z's political satisfaction, with perceptions of public opinion on social media serving as a mediating variable. A quantitative research design was employed using path analysis, with mediation effects assessed through the Sobel test. Data were collected from 400 Generation Z respondents residing in Semarang City and Semarang Regency. The results indicate that perceived government policies have a significant positive direct effect on Generation Z's political satisfaction. In contrast, perceptions of public opinion on social media significantly mediate this relationship through a negative indirect effect. These findings underscore the pivotal role of social media in shaping political evaluations and influencing the perceived legitimacy of government policies, highlighting the importance of effective digital communication strategies in strengthening public trust during the early stages of government.